Field Observations and Analyses of Water Quality Characteristics in a Dense Aquaculture Area Adjacent to a Coral Reef in Bolinao, Philippines - HERRERA, Eugene C.; NADAOKA, Kazuo; ASHIKAWA, Kota; VILLANOY, Cesar L.; SALAMANTE, Erlinda E.; YAMAMOTO, Takahiro (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
Bolinao is located along the north western coast of Luzon Island in the Philippines. Uncontrolled aquaculture has contributed to deterioration of water quality, indicated by massive milk fish kills and destruction of ecosystem of the Bolinao reef complex. The field observations were conducted around Santiago Island, Bolinao in order to evaluate the impacts of excessive milkfish culture on the coastal environment. High feeding input from fish cages or pens have contributed to nutrient enrichment and phytoplankton blooms not only in the aquaculture area but also right close to the reef area. It is known that dissolved oxygen should be more than 5 mg/l for milkfish growth. However, dissolved oxygen in the aquaculture area was less than this critical level from the surface to the bottom water especially during spring tide.